(3hUjI GdfGUM GdChO aj GdJMaX ef GdeQV GdhGaO (B( (3GdWGYhf(B) (3EPG haOs - (3CHh HcQ eMeO Hf YHjO Gddg Hf eMeO, GHf efXhQ GdbjSj,J (B750 (3g` s ((3Ydi Hf bGSe Hf Ydi GdHjGVj s)
(3ChdgG (B:s
(3GdMeO ddg GdQMje Gdebjd , eLjH OYhI GdOGYi EPG OYGg , heRjd GdEUQ GdKbjd s
(3BNQgG (B:s
(3adjTQM UOQc CjgG GdfGXQ ai gPG bQQfGg hSdGe Ydi YHGOg GdPjf GUWai s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3Cdag ai HjGf hLg GdJMaX ef GdhHGAs
(3hLYdg ai KdGKI aUhd hNGJeIs
(3hGdUaMI GdChdi HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs